2018
DOI: 10.1159/000492440
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Using a Nationwide Skin Cancer Screening Program: Findings from Germany

Abstract: Background: In 2008, a nationwide standardized and systematic skin cancer screening (SCS) service, which is globally unique, was implemented in Germany. We aimed to provide current data on SCS use, to explore barriers to SCS usage, and to identify population groups with lower rates of SCS use. Methods: We analyzed data from 2,635 participants (18-45 years) in the National Cancer Aid Monitoring on Sunbed Use. Data on SCS use, barriers to SCS, and sociodemographic characteristics were obtained. Chi-square tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In Germany, a biannual skin cancer screening is part of the healthcare routine of insurants aged 35 and over. The lifetime prevalence of skin cancer screening use here is about 39% . In addition to the whole body skin examination, dermatologists and physicians, who are enabled to perform this screening, are supposed to counsel their patients on primary prevention of skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In Germany, a biannual skin cancer screening is part of the healthcare routine of insurants aged 35 and over. The lifetime prevalence of skin cancer screening use here is about 39% . In addition to the whole body skin examination, dermatologists and physicians, who are enabled to perform this screening, are supposed to counsel their patients on primary prevention of skin cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several studies have explored the use of SCS within the German population, both from the perspective of those who underwent SCS and based on evaluation of data from health insurance companies. These studies reported SCS participation rates to range between 28% and 40% 10‐14 . In addition, regional differences in access to SCS have been revealed 15 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies reported SCS participation rates to range between 28% and 40%. [10][11][12][13][14] In addition, regional differences in access to SCS have been revealed. 15 One study focused on the provision of preventive counseling for skin cancer during SCS; however, the results were based on a relatively small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 In Germany for instance, several studies have reported on the underutilization of skin and colon cancer screening offers. [11][12][13][14] Gender-specific differences in cancer susceptibility are well known in cancer epidemiology. 15 Research shows that men are more likely to develop and die from cancer than women 3,15 , with only three types of cancers having a higher mortality rate in women than men.…”
Section: Introductionmentioning
confidence: 99%
“…Although cancer screening programs may effectively reduce the disease burden, utilization of available services remains low, even in high‐income countries with subsidized public healthcare systems 9,10 . In Germany for instance, several studies have reported on the underutilization of skin and colon cancer screening offers 11–14 …”
Section: Introductionmentioning
confidence: 99%